Processes in acceptance and commitment therapy and the rehabilitation of chronic fatigue. Issue 3 (June 2017) - Jacobsen, Henrik Børsting; Kallestad, Håvard; Landrø, Nils Inge; Borchgrevink, Petter C.; Stiles, Tore C.
Abstract : Acceptance and commitment therapy (ACT) has never been tested for patients with chronic fatigue. We aimed to test if a 3.5‐week ACT rehabilitation program for patients with chronic fatigue improved quality of life (QoL), fatigue, and psychological flexibility. Further, to test if improvements in QoL and fatigue were associated with improvement in psychological flexibility, and if psychological flexibility explained variance above and beyond maladaptive cognitions typically targeted in CBT for fatigue. Patients (n = 140) who had been on sick leave > 8 weeks due to chronic fatigue received a 3.5‐week non‐controlled inpatient rehabilitation program based on ACT. A physician and a psychologist examined the patients, assessing medication use and SCID‐I diagnoses. Patients completed questionnaires about somatic complaints, psychological complaints, and maladaptive cognitions before and after treatment. At post‐treatment, patients reported improved QoL ( p < 0.001; g = 1.07) and less fatigue ( p < 0.001; g = 1.08), but not increased psychological flexibility ( p = 0.6). Changes in psychological flexibility was associated with improved QoL, but not fatigue, in hierarchical regression analyses. When adjusting for other cognitions, changes in fear‐avoidance cognitions and all‐or‐nothing thoughts, but not psychological flexibility, were associated with improved QoL and fatigue. The ACT‐based treatment improved QoL and reduced fatigue for patients with chronic fatigue with large effect sizes. Improvement was associated with a reduction in fear‐avoidance cognitions and all‐or‐nothing thoughts, but not psychological flexibility.